The Importance of Bilateral Agreement on Mandatory Consular Notification for Indonesia: Tuti Tursilawati Execution - Yordan Gunawan; Zulfiani Ayu Astutik (Universitas Ahmad Dahlan, 2019)
Introduction to The Problem: The execution without notification of Tuti Tursilawatiâ€™s at the end of 2018 becomes one of the most important diplomatic and consular relations issues between Indonesia and Saudi Arabia. Indonesia was unable to seek Saudi Arabia clarification because of the absence of bilateral agreement regarding consular notification between Indonesia and Saudi Arabia. Having regard to the Vienna Convention on Diplomatic Relations 1961 and the Vienna Convention on Consular Relations 1963, both provides the protection and assistance from the Consulate to all their citizens abroad.Purpose/Objective Study: This research aims to outline the importance of bilateral agreement on the mandatory consular notification in dealing with a case of Tuti Tursilawati who executed by Saudi Arabia government without any notification to the Republic of Indonesia.Design/Methodology/Approach: Data was collected from primary and secondary data sources in the form of literature legal research and statute approach.Findings: The result shows that based on ArticleÂ 36 of the VCCR 1963, Mandatory Consular Notification should be delivered by Saudi Arabia before the execution. Making a bilateral agreement on Mandatory Consular Notification (MCN) with Saudi Arabia is very urgent to become a legal basis in helping and giving proper protection to the Indonesian who lives in Saudi Arabia in the future. Without that agreement, Indonesia will be not easy to access the information and assisting to protect the rights of the nationals from any cases that happened abroad, especially related to criminal issues.Paper Type: Research Article